RELATIONSHIPS OF CAUSALITY FROM LEVEL OF EDUCATION, REVENUES, AND CONSUMPTION TO THE QUANTITIES OF POOR PEOPLE IN THE COASTAL BEACH IN CITY OF BITUNG IN AEC FREE COMPETITION - Pangemanan, Sifrid S. (Journal of Asean Studies on Maritime Issues, 2017)
Poverty is a complex issue that is influenced by various interrelated factors, including the level of people's income, unemployment, health, education, access to goods and services, location, geography, and environment. The high level of poverty in North Sulawesi, indicated by the large number of poor people, shows the development process that has not been able to improve the welfare of its people. This study aims to analyze the direct and indirect effects of the average length of schooling, per capita GRDP, and per capita expenditure on the number of poor people in North Sulawesi City in 2017. The method of analysis in this study using path analysis using cross-district data in North Sulawesi in 2017 with the help of SPSS program application. Based on the results of data analysis found that education has a significant effect both directly and through income and consumption of the number of poor people, although the influence is still weak.Keywords: Consumption, education, income, poverty